Cytogenetic profile of patients with clinical spectrum of ambiguous genitalia, amenorrhea, and Turner phenotype: A 21‐year single‐center experience. Issue 8 (17th June 2019) - Elkarhat, Zouhair; Belkady, Boutaina; Charoute, Hicham; Zarouf, Latifa; Razoki, Lunda; Aboulfaraj, Jamila; Nassereddine, Sanaa; Elbakay, Chadli; Nasser, Boubker; Barakat, Abdelhamid; Rouba, Hassan
Abstract: The aim of the present study was to determine the frequency and nature of chromosomal abnormalities involved in patients with the clinical spectrum of ambiguous genitalia (AG), amenorrhea, and Turner phenotype, in order to compare them with those reported elsewhere. The study was conducted in the Cytogenetic Department of Pasteur Institute of Morocco, and it reports on the patients who were recruited between 1996 and 2016. Cytogenetic analysis was performed according to the standard method. Among 1, 415 patients, chromosomal abnormalities were identified in 7.13% (48/673) of patients with AG, 17.39% (28/161) of patients with primary amenorrhea (PA), 4% (1/25) of patients with secondary amenorrhea, and 23.20% (129/556) of patients with Turner phenotype. However, Turner syndrome was diagnosed in 0.89% (6/673) of patients with AG, 10.56% (17/161) of patients with PA, and 19.78% (110/556) of patients with Turner phenotype. In addition, Klinefelter syndrome and mixed gonadal dysgenesis were confirmed in 2.97% and 1.93% of patients, respectively, with AG, while, chimerism, trisomy 8, and trisomy 13 were confirmed only in 0.15% each. Trisomy 21 was confirmed in patients with AG and Turner phenotype (0.15% and 0.36%, respectively). Moreover, 5.60% (9/161) of patients with PA have been diagnosed as having sex reversal. Thus, the frequency of chromosomal abnormalities observed in Moroccan patients with PA is comparable to that reported in Tunisia, Turkey, Iran, and Hong Kong. However, the frequency is significantly less than that identified in India, Malaysia, Italy, and Romania.